Urban Impacts on Oxidative Balance and Animal Signals - Hutton, Pierce; McGraw, Kevin J. (Frontiers in Ecology and Evolution, 2016)
Though many animal ornaments and signals are sensitive to and encode information about the oxidative balance (OB) of individuals (e.g. antioxidant supplies/activity, reactive oxygen species, cellular oxidative damage/repair), often the environmental and/or physiological sources of such OB are unknown. Here we review the mechanistic underpinnings and functional consequences of how human urbanization drives antioxidant/oxidative status in animals and how this affects signal expression and use. Urban development is among the most recent, pervasive, and persistent human stressors on the planet and impacts many environmental and physiological parameters of animals. Here, we review literature on the potential effects of urbanization on OB and its linkage to signal expression and honesty in animals. Although we find that urbanization has strong negative effects on signal quality (e.g., visual, auditory, chemical) and OB across a range of taxa, few urban ecophysiological studies address signals and oxidative stress in unison, and even fewer in a fitness context. We also highlight particular signal types, taxa, life-histories, and anthropogenic environmental modifications on which future work integrating OB, signals, and urbanization could be centered. Last, we examine the conceptual and empirical framework behind the idea that urban conditions may disentangle signal expression from honesty and affect plasticity and adaptedness of sexually selected traits and preferences in the city.